Biologically Inspired Emotional Expressions for Artificial Agents - Korcsok, Beáta; Konok, Veronika; Persa, György; Faragó, Tamás; Niitsuma, Mihoko; Miklósi, Ádám; Korondi, Péter; Baranyi, Péter; Gácsi, Márta (Frontiers in Psychology, 2018)
A special area of human-machine interaction, the expression of emotions gains importance with the continuous development of artificial agents such as social robots or interactive mobile applications. We developed a prototype version of an abstract emotion visualization agent to express five basic emotions and a neutral state. In contrast to well-known symbolic characters (e.g. smileys) these displays follow general biological and ethological rules. We conducted a multiple questionnaire study on the assessment of the displays with Hungarian and Japanese subjects. In most cases participants were successful in recognizing the displayed emotions. Fear and sadness were most easily confused with each other while both the Hungarian and Japanese participants recognized the anger display most correctly. We suggest that the implemented biological approach can be a viable complement to the emotion expressions of some artificial agents, for example mobile devices.